Differences in the profile of cytokine expression induced by implantation of oncogenic and non-oncogenic millipore filters - E. Yu. Rybalkina; O. Yu. Susova; T. G. Moizhess (Успехи молекулярной онкологии)
Background. Clarification of the mechanisms of carcinogenesis induced by foreign bodies is one of the urgent problems of modern oncology. This is due to the fact that there is a relationship between the processes of inflammation and carcinogenesis. Today, there is no doubt the fact that cytokines and signal molecules in the focus of inflammation (products of inflammation) can contribute to the initiation of carcinogenesis, as well as stimulate tumor progression. In the case of carcinogenesis induced by foreign bodies, the key issue is understanding the differences in the body’s response to the implantation of foreign bodies that can cause tumor formation and do not have this ability. One of the phenomena of this type of carcinogenesis is the occurrence of sarcoma after the subcutaneous implantation in mice of hydrophilic millipore filters with a pore diameter not exceeding 0.1 μm and the inability to induce tumors of one’s with a pore diameter greater than or equal to 0.22 μm.The objective of our work was to study the differences between oncogenic and non-oncogenic filters at the molecular level.Materials and methods. Reverse transcription polymerase chain reaction method was used to study the expression of a number of cytokines that are products of macrophage cells that live on the surface of implanted filters and in the surrounding capsule. Filters with pore diameters of 0.025 μm (carcinogenic) and 0.45 μm (non-carcinogenic) were compared in 8, 35 days and 5.5 months after implantation.Results and conclusion. After 8 days we observed significant (p <0.01) excess of expression of two cytokines interleukin 1β (IL-1β) by cells around oncogenic filters (with pore of 0.025 μm) compared to non-oncogenic one’s (with pore of 0.45 μm) After 35 days, significant (p <0.01) excess of expression of IL-1β, Tnf-α, iNOS (induced nitric oxide synthase), and IL-6 by cells around the oncogenic filters (0.025 μm) compared to non-oncogenic one’s (0.45 μm) was observed. There was no quantitative difference in the expression of Nf-κB1 and Nf-κB2 (nuclear factor κ-B1, κ-B2), Tgf-β (transforming growth factor β), IL-10. After 5.5 months the expression of IL-1β by cells on oncogenic filters was still significant; for Tnf-α, iNOS, IL-6 and IL-10 there was no practically difference in expression. For Nf-κB1 and Nf-κB2, Tgf-β and COX-2 (cyclooxygenase 2) the difference was significant, cells on non-oncogenic filters are expressed more then on oncogenic one’s.